Symbiotic potential of endophytic fungi from native orchids with histological insights and growth responses in Dendrobium hybrid - DWI SUCIANINGTYAS SUKAMTO; SHOLEH AVIVI; SUHARTININGSIH DWI NURCAHYANTI; DIDIK PUDJI RESTANTO (Society for Indonesian Biodiversity, 2025)
Abstract. Sukamto DS, Avivi S, Nurcahyanti SD, Restanto DP. 2025. Symbiotic potential of endophytic fungi from native orchids with histological insights and growth responses in Dendrobium hybrid. Biodiversitas 26: 6389-6398. Endophytic fungi play an essential role in orchid development by facilitating nutrient exchange and supporting early growth through peloton formation in root tissues. This study evaluated the symbiotic potential of eight fungal isolates obtained from native orchids in Jember, East Java, Indonesia, and examined their effects on peloton induction, root colonization, and seedling growth of a Dendrobium hybrid. Each isolate was identified morphologically and tested through inoculation assays, histological analyses, and seedling performance measurements. Four isolates—Ceratobasidium (1), Rhizoctonia sp. (3 and 4), and Tulasnella (6)—successfully colonized the root cortex and produced pelotons, whereas isolates 2 (Fusarium) and 8 (Cladosporium) caused pathogenic symptoms, including root and leaf rot, and were excluded from growth evaluation. Growth assays showed that Rhizoctonia isolate 4 produced the strongest symbiotic response, increasing shoot number by 175% and shoot length by more than tenfold relative to controls, followed by moderate enhancements from isolates 1, 5, 6, and 7. These findings show that native orchid-associated endophytes possess strong mycorrhizal potential and can be developed as effective bioinoculants to enhance the early growth of Dendrobium hybrids. This study provides a foundational step toward utilizing locally sourced symbiotic fungi to support orchid propagation and conservation efforts.